'Don't call me resilient again!': the New Urban Agenda as immunology … or … what happens when communities refuse to be vaccinated with 'smart cities' and indicators. (April 2017) - Kaika, Maria
The Habitat III Conference's New Urban Agenda hails a "paradigm shift" for pursuing the Sustainable Development Goals (SDGs). However, the new call for "safe, resilient, sustainable and inclusive cities" remains path dependent on old methodological tools (e.g. indicators), techno-managerial solutions (e.g. smart cities), and institutional frameworks of an ecological modernization paradigm that did not work. Pursuing a new urban paradigm within this old framework can only act as immunology: it vaccinates citizens and environments so that they can take larger doses of inequality and degradation in the future; it mediates the effects of global socio-environmental inequality, but does little towards alleviating it. Indeed, an increasing number of communities across the world now decline these immunological offers. Instead, they rupture path dependency and establish effective alternative methods for accessing housing, healthcare, sanitation, etc. I argue that real smart solutions and real social innovation are to be found not in consensus-building exercises, but in these dissensus practices that act as living indicators of what/where urgently needs to be addressed.